PREDICTORS OF SEPSIS IN PATIENTS WITH URGENT CONDITIONS - G. V. Bulava; M. V. Androsova; A. K. Shabanov; O. V. Nikitina; I. V. Alexandrova (Неотложная медицинская помощь, 2017)
Background. Given that the imbalance in pro- and anti-inflammatory cytokines plays an important role in the pathogenesis of sepsis, estimation of its prognostic value in patients in the early stages from the disease onset or injury is of concern.Aim of study. To study changes in concentrations of biomarkers for inflammation on day 1–2 in patients with a high risk for sepsis.Materials and methods. On day 1-2 from the admission, blood tests were performed in 48 patients with a high risk of sepsis: 9 — with mediastinitis, 6 — with widespread purulent peritonitis, 24 — with severe concomitant injury, 9 — with acute destructive pancreatitis. Sepsis occurred in 28 patients of group 1. Group 2 consisted of 20 patients without sepsis. We investigated concentration of procalcitonin, C-reactive protein, interleukine-6 and -10, lipopolysaccharide-bindidng protein and soluble receptor for interleukine-2.Result. Significant differences in concentrations of groups were identified on day 1-2 in CRP (P=0.00009), IL-2R (P=0.0005) LBP (P=0.00002) and IL-6 (P=0.0192).Conclusion. Hyper LBP and CRP on the background of high IL-2R, IL-6, increase the risk of sepsis.